Identification of Garden Plant Diversity in Tamansari Village, Karanganyar Regency as a Biology Learning Resource for Biodiversity Material - Fitriani, Rindi Diah Ayu; Hanik, Nur Rokhimah; Nugroho, Anwari Adi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Garden plants are plants that can adapt to the local environment and have economic, social and ecological functions. This research aims to identify garden plants in Tamansari Village, Kerjo District, Karanganyar Regency. This research activity was carried out for 3 months, namely Februari 2024-April 2024. The study was conducted at Tamansari Village, which has nine hamlets, including Glagah Hamlet., Sidomulyo Hamlet, Mbabadan Hamlet, Jambewangi Hamlet, Nggiren Hamlet, Ngrandah Hamlet, Taman Hamlet, Sidi Hamlet, and Klebrekan Hamlet. The method used in this research is exploratory descriptive with survey/observation and interview methods as supporting data. The number of yards observed was 40 residents' house yards with 5 categories of plants, namely fruit plants, vegetable plants, medicinal plants, shade plants and ornamental plants. From these 5 plant categories, 87 species of garden plants were obtained. From the research results, the plants most frequently identified were 37 types of ornamental plants, 21 types of fruit plants, 13 types of medicinal plants, 8 types of vegetables, and 5 types of shade plants.